Unprecedented ferrocene-quinoline conjugates: facile proton conduction via 1D helical water chains and a selective chemosensor for Zn(II) ions in water - Ponniah, Joseph S.; Barik, Subrat Kumar; Borthakur, Rosmita; Thakur, Arunabha; Garai, Bikash; Janaa, Sourita; Ghosh, Sundargopal (RSC Advances, 2015)
Two novel ferrocene-quinoline derivatives 3 (C22H19O2N3Fe) and 4 (C34H28O4N6Fe) have been synthesized and structurally characterized. Compound 3 exhibits good proton conductivity through 1D helical water chains. In addition, both compounds 3 and 4 selectively detect Zn2+ ions in water with a detection limit of 2 ppb through multiple channels.